Penerapan Metode Service Quality pada UD. Triple-X untuk Mengukur Tingkat Kepuasan Pelanggan - Muhammad Daffa Ardiansyah; Elly Ismiyah; Akhmad Wasiur Rizqi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
In today's era of global business competition, industrial companies must always keep up in a better direction so that they can survive in the midst of innovation rapid changes. This also applies to companies in the field of bag production. Every year, the presence of bags of various designs provides a blend of functionality, creativity, quality, modernity, as well as simplicity. The increasing number of products and product variants stems from the increasing number of needs for the use of bags. From observations on partners activities, a number of consumer complaints were obtained including product quality, service that was less representative, and product prices that were less affordable. As a result, sales decreased by 20% in the period of October, November, and December 2021. However, to determine and test the role of satisfaction, as the cause of the decline in sales, it is necessary to carry out a structured measurement. One way is through the use of the Servqual method. The results of the case studies applied to partners showed that there was a negative servqual value. Actions need to be taken to overcome all attributes that have a negative gap value, which is formulated as a proposed improvement. Partners accept improvement proposals well.